Comparison of the Frequency of Temporomandibular Disorders Between β-Thalassemia Major Patients and High School and Guidance School Students - S Salimzadeh; H SHeykhNezhad; Z Zohri; P Salimzadeh (Islamic Azad University, 2019)
Background and Aim: Patients affected by thalassemia major show great skeletal changes in the head and neck area in addition to malocclusion. It seems that examination of malocclusion in these patients and evaluation of the frequency of temporomandibular disorders (TMD) can help identify people with a high risk of illness in the society. The current study aimed to compare the frequency of TMD between β-thalassemia major patients and high school and guidance school students. Materials and Methods: In this descriptive-analytical study, 51 patients affected by thalassemia major (23 girls and 28 boys) and 78 normal (43 girls and 35 boys) guidance and high school students between 12 and 18 years old were evaluated. The presence of TMD and malocclusion and their relationship were determined. After examination and completion of the related questionnaire, data were analyzed by chi-square test and t-test using SPSS software. Results: According to the data, there was no significant difference in spacing, occlusion, crowding, open bite, headache, bruxism, crepitation, clicking, TMD, subluxation, locking, cleaning, deviation, deep bite, and crossbite between the control and thalassemia students (P>0.05). However, significant differences were observed regarding overjet and pain (P<0.05). Conclusion: These results suggest that TMD and occlusion type have no significant correlation with thalassemia.